Development of a single-vertebra image-based technique to quantify shoulder kinematics using four-dimensional computed tomography - James Hunter; Ting-Yim Lee; George S. Athwal; Emily A. Lalone (Computer Methods in Biomechanics and Biomedical Engineering: Imaging & Visualization, 2024)
This paper introduces and validates a new technique for analysing six degrees-of-freedom shoulder kinematics using four-dimensional computed tomography (4DCT), which uses a single vertebra to reference thoracic motion. Differences between the vertebra and International Society of Biomechanics (ISB) torso coordinate systems had an average RMSE of 11.6º and no statistical differences were found regarding range of motion. The errors associated with repeated analysis ranged from 0.2 mm to 3.4 mm, and 0.9º to 1.1º. Overall, the technique has been shown to be repeatable, and using a single vertebra is comparable to using the ISB torso coordinate system.